Study of LED Grow Light Driver Circuit for Indoor Strawberry Cultures: A Class Experiment - S. Sungwiset; T. Janprung; T. Pechsiri; S. Puengsungewan (Universitas Pendidikan Indonesia (UPI), 2021)
This journal presents the study of the led driver circuits for strawberry LED grow light. There are three driver circuits: A linear resistor circuit, a simple transistor circuit, and a boost converter circuit. Boost converter circuits are more efficient than direct drives and transistor drives. Because the circuit can be controlled from a 40 kHz PMW signal that gives a more constant value and circuit stability. There is also less load in the circuit, making less loss in the circuit with a high-efficiency value. When the voltage used is 12 volts, we got a value of Photosynthetic Photon Flux Density (PPFD) of 230 μmol/m2/s. This circuit has very high efficiency (98%). The boost converter is suitable for driving LED bulbs for strawberry planting.